2011
DOI: 10.1002/pon.1969
|View full text |Cite
|
Sign up to set email alerts
|

Initial evaluation of an Internet intervention to improve the sleep of cancer survivors with insomnia

Abstract: Objective Insomnia is a common complaint among cancer survivors. Fortunately, cognitive-behavioral therapy for insomnia (CBT-I) has been shown to be an effective treatment in this population. However, it is rarely implemented given its limited availability. To address this barrier, we examined the ability of an easily-accessible online CBT-I program to improve insomnia symptoms in cancer survivors. Methods Twenty-eight cancer survivors with insomnia were randomly assigned to either an Internet insomnia inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
283
3
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 258 publications
(316 citation statements)
references
References 58 publications
19
283
3
11
Order By: Relevance
“…Three randomised controlled trials (RCT) investigating the effect of CBT on insomnia included men with prostate cancer. Of these, Garland et al included 8 men with prostate cancer (7% of total) [59] and Ritterband et al included 4 men [60] , but the cancer site was not identified and neither trial presented results specifically for men with prostate cancer. One RCT encompassed 150 patients with cancer at mixed sites including men with prostate cancer (N = 34; 23%) suffering from insomnia for at least 6 months [53] .…”
Section: Management Of Insomnia Among Men With Prostate Cancermentioning
confidence: 99%
“…Three randomised controlled trials (RCT) investigating the effect of CBT on insomnia included men with prostate cancer. Of these, Garland et al included 8 men with prostate cancer (7% of total) [59] and Ritterband et al included 4 men [60] , but the cancer site was not identified and neither trial presented results specifically for men with prostate cancer. One RCT encompassed 150 patients with cancer at mixed sites including men with prostate cancer (N = 34; 23%) suffering from insomnia for at least 6 months [53] .…”
Section: Management Of Insomnia Among Men With Prostate Cancermentioning
confidence: 99%
“…3 Recently, online CBT has shown promising results. [4][5][6] We conducted the first randomized placebo controlled trial of online CBT demonstrating significant improvements in both sleep pattern and daytime functioning. 7 Consistent with the formulation of insomnia as a psychophysiological condition, we feel it is important to reflect not only upon the impact of CBT on sleep, but also its impact on a range of secondary outcomes that are likely maintaining factors, such as attribution, cognition and psychopathological status.…”
Section: Introductionmentioning
confidence: 99%
“…With regards to behavioral interventions which now largely are considered the treatment of choice for persistent insomnia [33], cognitive-behavioral therapy addressing both pain and sleep, has been found to be effective [32]. Future research should examine to what extent low threshold interventions addressing comorbid sleep and pain may be effective, as internet-based self-help treatments have shown promising results in treating both conditions individually [34][35][36]. Moreover, given the significant contribution of depressive symptoms in explaining the observed sleep-pain association, we also recommend screening for depression during and after pregnancy, in addition to adequately identifying, preventing and treating insomnia for this population.…”
Section: Discussionmentioning
confidence: 99%